Atg9 antagonizes TOR signaling to regulate intestinal cell growth and epithelial homeostasis in Drosophila. - Wen, J.K.; Wang, Y.T.; Chan, C.C.; Hsieh, C.W.; Liao, H.M.; Hung, C.C.; Chen, G.C. (eLife, 2017)
Autophagy is essential for maintaining cellular homeostasis and survival under various stress conditions. Autophagy-related gene 9 (Atg9) encodes a multipass transmembrane protein thought to act as a membrane carrier for forming autophagosomes. However, the molecular regulation and physiological importance of Atg9 in animal development remain largely unclear. Here, we generated Atg9 null mutant flies and found that loss of Atg9 led to shortened lifespan, locomotor defects, and increased susceptibility to stress. Atg9 loss also resulted in aberrant adult midgut morphology with dramatically enlarged enterocytes. Interestingly, inhibiting the TOR signaling pathway rescued the midgut defects of the Atg9 mutants. In addition, Atg9 interacted with PALS1-associated tight junction protein (Patj), which associates with TSC2 to regulate TOR activity. Depletion of Atg9 caused a marked decrease in TSC2 levels. Our findings revealed an antagonistic relationship between Atg9 and TOR signaling in the regulation of cell growth and tissue homeostasis.